Nanoporous Surface High‐Entropy Alloys as Highly Efficient Multisite Electrocatalysts for Nonacidic Hydrogen Evolution Reaction - Yao, Rui‐Qi; Zhou, Yi‐Tong; Shi, Hang; Wan, Wu‐Bin; Zhang, Qing‐Hua; Gu, Lin; Zhu, Yong‐Fu; Wen, Zi; Lang, Xing‐You; Jiang, Qing (Advanced functional materials, 2021)
Electrocatalytic hydrogen evolution in alkaline and neutral media offers the possibility of adopting platinum‐free electrocatalysts for large‐scale electrochemical production of pure hydrogen fuel, but most state‐of‐the‐art electrocatalytic materials based on nonprecious transition metals operate at high overpotentials. Here, a monolithic nanoporous multielemental CuAlNiMoFe electrode with electroactive high‐entropy CuNiMoFe surface is reported to hold great promise as cost‐effective electrocatalyst for hydrogen evolution reaction (HER) in alkaline and neutral media. By virtue of a surface high‐entropy alloy composed of dissimilar Cu, Ni, Mo, and Fe metals offering bifunctional electrocatalytic sites with enhanced kinetics for water dissociation and adsorption/desorption of reactive hydrogen intermediates, and hierarchical nanoporous Cu scaffold facilitating electron transfer/mass transport, the nanoporous CuAlNiMoFe electrode exhibits superior nonacidic HER electrocatalysis. It only takes overpotentials as low as ≈240 and ≈183 mV to reach current densities of ≈1840 and ≈100 mA cm−2 in 1 m KOH and pH 7 buffer electrolytes, respectively; ≈46‐ and ≈14‐fold higher than those of ternary CuAlNi electrode with bimetallic Cu–Ni surface alloy. The outstanding electrocatalytic properties make nonprecious multielemental alloys attractive candidates as high‐performance nonacidic HER electrocatalytic electrodes in water electrolysis. Nonprecious nanoporous multielemental alloy electrodes composed of electroactive surface high‐entropy CuNiMoFe alloy hold great promise as cost‐effective electrocatalysts for hydrogen evolution reaction (HER) in nonacidic media. Associated with hierarchical nanoporous architecture to facilitate electron transfer and offer abundant high‐entropy CuNiMoFe active sites, the nanoporous CuAlNiMoFe hybrid electrode exhibits remarkably enhanced HER activity and durability.